1982
DOI: 10.1139/v82-352
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chemical shift correlation maps from heteronuclear two-dimensional nuclear magnetic resonance spectroscopy. II: Carbon-13 and proton chemical shifts of a-D-glucopyranose oligomers

Abstract: Double Fourier transform ("2D") nmr methods allow the simultaneous measurement of proton and carbon-13 chemical shifts for each directly bonded carbon–proton pair in a molecule. As well as greatly increasing the number of different resonances that may be distinguished in the spectra of complex systems, the measurement of correlated proton and carbon-13 shifts allows the otherwise inaccessible proton shifts to be determined, and facilitates the assignment of conventional proton and carbon-13 spectra. Results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…4. The chemical shift of authentic maltotriose almost agreed with that from the study by l\10rris et al 15 ) If the phosphate group in S l was linked to C-3 of the glucosyl residue, the carbon signals of C-2, C-3, and C-4 of the glucosyl residue would have exhibited a split into peaks and/or a shift. If the phosphate group was linked to C-2 of the glucosyl residue, the carbon signals of C-l, C-2, and C-3 of the glucosyl residue would also have exhibited a split into peaks and/or a sh:lf1.…”
Section: ) Detennination Of the Non-reducing-terminal Residue (Rapidsupporting
confidence: 84%
“…4. The chemical shift of authentic maltotriose almost agreed with that from the study by l\10rris et al 15 ) If the phosphate group in S l was linked to C-3 of the glucosyl residue, the carbon signals of C-2, C-3, and C-4 of the glucosyl residue would have exhibited a split into peaks and/or a shift. If the phosphate group was linked to C-2 of the glucosyl residue, the carbon signals of C-l, C-2, and C-3 of the glucosyl residue would also have exhibited a split into peaks and/or a sh:lf1.…”
Section: ) Detennination Of the Non-reducing-terminal Residue (Rapidsupporting
confidence: 84%
“…With the exception of the three trehaloses (2)(3)(4), it was observed that the reducing anomeric a-carbon usually resonates in the region 90.1-92.9 ppm while the b-carbon resonates at 95.3-96.9 ppm ( Table 1). The a-linked anomeric carbon of the non-reducing end resonates in the region 97.0-104.6 ppm, while the b-linked non-reducing anomeric carbon resonates at 98.4-103.5 ppm ( Table 1).…”
Section: Nmr Results and Discussionmentioning
confidence: 99%
“…Moreover, most of the published data available are contradictory. [3][4][5][6][7][8][9][10][11][12] Part of the published data is from selectively protected sugars, for example, sugars methylated at the anomeric center to hinder mutarotation and so enabling assignment of the a-and b-anomerically pure saccharides separately with less overlapping signals. The 13 C chemical shifts of some anomerically locked glucosyl glucosides have been determined using dynamic NMR, and they have also been compared with those of the monomer D D-glucose.…”
Section: Introductionmentioning
confidence: 99%
“…We have used two-dimensional (2D) nuclear proton correlation (COSY) (12), relayed correlation spectroscopy (RECSY) (1 3), J-resolved (1 2), nuclear Overhauser enhancement (NOESY) (14), and one-dimensional nuclear Overhauser enhancement experiments to determine the complete sugar sequence and the sites of interglycosidic linkage, thus obviating the need for hydrolysis reactions. In one case (forbeside B), we have utilized a hydrogen-carbon correlation (HCORR) (15) (10,16). 2D nuclear magnetic resonance has enjoyed much success in the structural elucidation of a variety of natural products (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In one case (forbeside B), we have utilized a hydrogen-carbon correlation (HCORR) (15) (10,16). 2D nuclear magnetic resonance has enjoyed much success in the structural elucidation of a variety of natural products (16)(17)(18)(19)(20). In this paper we illustrate the utility of 2D techniques for the complete structural elucidation of marine saponins.…”
mentioning
confidence: 99%